A Comparison of Pressure Mapping Between Two Pressure-Reducing Methods for the Sacral Region. Issue 4 (July 2015) - Bush, Tamara Reid; Leitkam, Samuel; Aurino, Michael; Cooper, Andrew; Basson, Marc D.
<x xml:space="preserve">Abstract</x> PURPOSE: The objective of this study was to quantify tissue interface pressures that occurred in the sacrum, shoulder, and buttock/thigh regions while using (1) pillows or (2) a wedge system for off-loading of sacral pressures. SUBJECTS AND SETTING: Twenty-one volunteers (11 females and 10 males) residing near a Midwestern, university community consented to participate in the study. Testing was conducted in a hospital bed with pillows and a commercially available wedge system. METHODS: Pressures were measured under 3 test conditions: (1) bed alone, (2) pillows positioned above and below the sacral region, and (3) wedges positioned above and below the sacral region. Each condition was tested with the elevation of the head of the bed at 3 different angles with respect to the foot of the bed (0°, 20°, and 30°). Two pressure mats were used to capture data; one was located in the shoulder region and the other in the sacral/buttocks/thigh region. RESULTS: Between the pillows and the wedge, the wedge system was the most effective in reducing pressures on the sacral area. In comparison to the bed condition, both the pillow and wedge conditions produced significantly lower mean sacral pressures than the bed alone (P < .05). Because the pillow and wedge systems tilted the body onto one side, higher pressures were identified on the buttock/thigh when compared to the bed alone (P < .05). CONCLUSIONS: Pressure reduction occurred in the sacral region with the pillow and wedge systems; however, this reduction resulted in increased pressures in the posterior-lateral regions of the buttocks and thighs. When using off-loading devices, consideration should be given to all factors, including tissue interface pressures on the sacrum, increased pressures on other body locations, and the likelihood that these increased pressures will result in tissue damage.